Sr2Fe1.5Mo0.5O6-δ - Sm0.2Ce0.8O1.9 Composite Anodes for Intermediate-Temperature Solid Oxide Fuel Cells - He, Beibei; Zhao, Ling; Song, S.; Liu, T.; Chen, F.; Xia, C. (The Electrochemical Society, Inc, 2012)
Sr2Fe1.5Mo0.5O6−δ (SFM) perovskite is carefully investigated as an anode material for solid oxide fuel cells with LaGaO3-based electrolytes. Its electronic conductivity under anodic atmosphere is measured with four-probe method while its ionic conductivity is determined with oxygen permeation measurement. Samaria doped ceria (SDC) is incorporated into SFM electrode to improve the anodic performance. A strong relation is observed between SDC addition and polarization losses, suggesting that the internal SFM-SDC contacts are active for H2 oxidation. The best electrode performance is achieved for the composite with 30 wt% SDC addition, resulting in an interfacial polarization resistance of 0.258 Ω cm2 at 700°C for La0.8Sr0.2Ga0.8Mg0.2O3−δ supported single cells. Electrochemical impedance spectroscopy analysis indicates that the high performance of SFM-SDC composite anodes is likely due to the high ionic conductivity and electro-catalytic activity of SDC by promoting the ionic exchange processes. Redox cycle treatment shows that SDC addition can even improve the redox tolerance of SFM anodes.